The Need For Indonesian Language Textbooks For Elementary School School Students In Lebak District - siti Maemunah; Lisa Novia (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to examine the characteristics of Indonesian language textbooks used by fourth-grade elementary school students in Lebak Regency, focusing on material relevance, language accessibility, variety of learning activities, and visual presentation. The approach used was descriptive qualitative with content analysis. Data were obtained through document review of the textbooks used and reinforced by interviews with teachers to obtain a more contextual picture of learning. The research findings indicate that, in general, the textbooks adhere to curriculum standards and present material in a structured manner. However, the learning content is still dominated by general national themes and does not optimally accommodate the local socio-cultural context. The activities presented also focus more on literal understanding, so opportunities for developing higher-order thinking skills are still limited. In terms of language, the use of sentences is relatively simple and appropriate to the students' developmental level, although some sections still require additional explanation from the teacher. Meanwhile, the visual aspect is quite helpful in supporting understanding, but does not yet strongly represent the richness of local culture. Based on these results, this study recommends the need to develop textbooks that are more oriented towards contextual learning, strengthening the representation of local culture, and increasing activities that encourage critical thinking skills to support the effectiveness of learning at the elementary education level.